Training, wages and a missing school graduation cohort - Matthias Dorner; Katja Görlitz (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
This study analyzes the effects of a missing high school graduation cohort on firms' training provision and trainees' wages. An exogenous school reform varying at the state and year level caused the missing cohort to occur. Using administrative social security data on all trainees and training firms, we show that firms provide less training by reducing their overall number of hired apprentices. We also show that the pool of firms that offer training in the year of the missing cohort shifts towards a higher share of low wage firms. After keeping firm characteristics constant, the findings indicate that the missing cohort increases training wages measured at the start of training. Further analyses shed light on the opposite case of dual cohorts, which we find to increase training provision and to decrease training wages. The evidence also shows that high and low wage firms differ in how they adjust training provision in response to a dual cohort. – – Die Studie untersucht die Auswirkungen einer fehlenden Abiturientenkohorte auf die Zahl der neu eingestellten Auszubildenden und deren Löhne. Grund für die fehlende Kohorte ist eine exogene Schulreform, die auf Jahres- und Bundeslandebene variierte. Schätzungen basierend auf den administrativen Daten aller sozialversicherungspflichtig Beschäftigten zeigen, dass die Betriebe ih-ren Ausbildungsbedarf nicht decken konnten, da die Zahl der eingestellten Auszubildenden im Vergleich zu den Vorjahren sank. Darüber hinaus legen die Ergebnisse nahe, dass Betriebe, die trotz der fehlenden Kohorte ausbilden, in der Regel geringere Löhne zahlen. Nachdem dafür kontrolliert wurde, zeigt sich, dass die fehlende Kohorte die Betriebe dazu veranlasst hat, über höhere Ausbildungsvergütungen um die geringere Zahl an Abiturienten zu konkurrieren. Weitere Untersuchungen beleuchten den umgekehrten Fall einer dualen Kohorte, bei der sich eine Erhöhung der neu eingestellten Auszubildenden und eine Senkung der Ausbildungslöhne feststellen lässt.
Keywords: J21; J24; J31; 330; Training wages; training provision; missing high school graduation cohort; high and low wage firms; dual high school graduation cohort